Polarimetric Channel Imbalance Evaluation of GF-3 SAR Products by Bragg-Like Targets - Hanglan Guo; Xingjie Zhao; Xiuqing Liu; Weidong Yu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Polarimetric calibration is crucial to ensure the accuracy and reliability of subsequent application results. Since Gaofen-3(GF-3) has been providing polarimetric Synthetic Aperture Radar images for six years, it is necessary to monitor the polarimetric performance by estimating the residual channel imbalance. In this article, we proposed an improved algorithm based on zero helix component of Bragg-like targets. The method can provide transmitting and receiving channel imbalances results and can be applied to the large-scale polarimetric evaluation. We verified the effectiveness of the algorithm and assessed the residual channel imbalance in the multibeam polarimetric products of GF-3 quad-polarimetric Stripmap from 2019 to 2023. The experiments indicate that the residual channel imbalance changes in the same strip observation and the polarimetric performance remains stable. The evaluation conclusions can be used as references for subsequent application of GF-3 polarimetric products.